Determinants of privatized solid waste management service provision in Lagos - Usman, Adam Shehu; Shamsudin, Mad Nasir; Ahmad Sidique, Shaufique Fahmi; Abdul Rahim, Khalid; Radam, Alias (Routledge, 2015)
The growing popularity of privatized solid waste management service in least developed countries warrants an exploration of factors that are likely to impact on its sustainability. This study takes integrated solid waste management approach by analyzing relevant issues on both market sides. We use a three step theme development sequence to analyze the data obtained on service providers through library research, observations and interviews. This was followed by an opinion survey on the demand side to elicit households’ support for service improvement. Findings show that source-separation issues, government enforcement, market segmentation, financial issues and waste disposal issues are key factors influencing improved service provision. Meanwhile, on the demand side, we found that households are willing to support proposed regulatory improvement in service provision. Thus, we suggest industrial stakeholders to consider the aforementioned supply side issues in designing future service improvements that will take advantage of existing demand side feasibility.